Experimental study on vibration instability model of rock slope based on parallel chaotic algorithms. (November 2019) - Han, Liu; Chen, Shuzhao; Shu, Jisen; Shang, Tao
Abstract: In view of the irrationality of sensor arrangement scheme in the model test method of anti-dip rock slope vibration instability, the accuracy and efficiency of test data acquired are reduced, which cannot meet the requirements of real-time vibration simulation process. There are some limitations in the authenticity and scientificity of test results. A model test of rock slope vibration instability based on parallel chaotic algorithm is proposed. The method uses cement, sand, iron powder, clay and admixture to prepare rock mass materials, sets Teflon cloth with very low surface friction coefficient to simulate discontinuous joints of rock slope according to certain rules in the interior of slope, and adopts parallel chaotic genetic algorithm to optimize sensor placement scheme based on the corresponding relationship between algorithm and optimal parameters of sensor placement. The experimental results show that the failure modes of rock slope under vibration are as follows: crack development, slope spalling and collapse sliding; acceleration response enlarges obviously along the slope face, and horizontal acceleration dominates; the optimization effect and operation time of sensor placement scheme are significantly improved to avoid premature convergence and fall into local optimum solution.